Ectoparasites in Nile tilapia (Oreochromis niloticus) from Chitralada and GIFT strains, in different densities, fed with two protein levels - DOI: 10.4025/actascianimsci.v29i4.1015 - Braccini, Graciela Lucca (2008)
Ectoparasites infestation in Nile Tilapia (Oreochromis niloticus) was observed in Chitralada and GIFT strains cultivated in cages and ponds, using rations with two protein levels. During the assay, temperature, pH, dissolved oxygen and electric conductivity were analyzed. Tegument scraping and gill samples from reverted males were evaluated, in two experiment phases. The first phase was carried out with 240 fingerlings from 18 500 L fiberglass boxes using three stocking densities. Total prevalence of parasites in the Chitralada strain (stocking density of 30, 40 and 50 fish m-3) was 72.2, 83.3 and 59.5%, with Trichodina predominance (38.9, 63.3 and 26.2%), respectively. For the GIFT strain, at the same stocking density, 83.3, 73.3 and 80.9% were observed, with higher Trichodina predominance (33.3, 73.3 and 45.2%), respectively. In the second phase, 90 fish from each strain, from two ponds (140 m2 each) and fed with two crude protein levels (25 and 30%) were evaluated. Total prevalence for Chitralada and GIFT strains with 25% CP was 86.7 and 76.7, respectively, and for 30% CP was 60%. The 30% CP level, regardless of strain, had the lowest parasite prevalence.